De la leve existencia (incluso legal) del Patrimonio Inmaterial - Francesc Llop i Bayo (Erebea. Revista de Humanidades y Ciencias Sociales, 2018)
Newly recognized Intangible Heritage is the poor sister of the heritage, the least appreciated and protected category. There is a contradiction that everyone claims to protect it, but in reality it is subject to limitations and lack of protection that recognized patrimony, especially the monumental one does not have.